Ambient air pollution, traffic noise and adult asthma prevalence: a BioSHaRE approach. Issue 1 (12th January 2017) - Cai, Yutong; Zijlema, Wilma L.; Doiron, Dany; Blangiardo, Marta; Burton, Paul R.; Fortier, Isabel; Gaye, Amadou; Gulliver, John; de Hoogh, Kees; Hveem, Kristian; Mbatchou, Stéphane; Morley, David W.; et al.
We investigated the effects of both ambient air pollution and traffic noise on adult asthma prevalence, using harmonised data from three European cohort studies established in 2006–2013 (HUNT3, Lifelines and UK Biobank). Residential exposures to ambient air pollution (particulate matter with aerodynamic diameter ≤10 µm (PM10 ) and nitrogen dioxide (NO2 )) were estimated by a pan-European Land Use Regression model for 2007. Traffic noise for 2009 was modelled at home addresses by adapting a standardised noise assessment framework (CNOSSOS-EU). A cross-sectional analysis of 646 731 participants aged ≥20 years was undertaken using DataSHIELD to pool data for individual-level analysis via a "compute to the data" approach. Multivariate logistic regression models were fitted to assess the effects of each exposure on lifetime and current asthma prevalence. PM10 or NO2 higher by 10 µg·m −3 was associated with 12.8% (95% CI 9.5–16.3%) and 1.9% (95% CI 1.1–2.8%) higher lifetime asthma prevalence, respectively, independent of confounders. Effects were larger in those aged ≥50 years, ever-smokers and less educated. Noise exposure was not significantly associated with asthma prevalence. This study suggests that long-term ambient PM10 exposure is associated with asthma prevalence in western European adults. Traffic noise is not associated with asthma prevalence, but its potential to impact on asthma exacerbations needs further investigation. Long-term ambient PM10 exposure is associated with asthma prevalence in three European adult cohorts http://ow.ly/En4b3049S7X